Some Convergent Summation Theorems For Appell’s Function F1 Having Arguments 􀀀1; 1 2 - Qureshi, M.I.; Baboo, M.S.; Ahmad, A. (Karagandy University of the name of acad. E.A. Buketov, 2022)
In this paper, we obtain some closed forms of hypergeometric summation theorems for Appell’s function of first kind F1 having the arguments 􀀀1; 1 2 with suitable convergence conditions, by adjustment of parameters and arguments in generalized form of first, second and third summation theorems of K¨ummer and others.
−1, 1 2 аргументтерi бар F1 Апелль функциясына арналған кейбiр конвергенттi қосындылар теоремалары
Некоторые теоремы о сходящемся суммировании для функции Аппеля F1 с аргументами −1,1 2
Keywords: generalized hypergeometric function; Appell’s function of first kind; K¨ummer’s first; second and third summation theorems.